Complexes of cobalt(II), nickel(II) and copper(II) with 3-hydroxysalicyliden-p-aminoacetophenoneoxime - Tuna, S; Canpolat, E; Kaya, M (Polish Chemical Soc, 2006)
The complexes of CO(II), Ni(II) and Cu(II) with 3-hydroxysalicyliden-p-aminoacetophenoneoxime were prepared and characterized by physical, spectral and analytical data. The metal: ligand stoichiometric ratio is 1:2 in all the complexes. It was determined that the bidentate behavior of the ligand is accomplished via the phenolic oxygen and the azomethine nitrogen atoms. The presence of water is revealed by thermograms and supported by the presence of relevant bands in their IR spectra. Suitable structures have been proposed for these complexes.
Keywords: Schiff base; transition metal complexes